Tinjauan Komprehensif Tentang Model Kematangan Budaya Keselamatan di Sektor Pertambangan - Muhammad Osaegi Restu Amrulloh; Endik Riyanto (Journal of Educational Innovation and Public Health, 2024)
Many researchers are interested in evaluating the quality of safety cultures, particularly in the mining industry. Keputusan Dirjen Minerba Nomor 185 Tahun 2019, in Element II of the initial review section, has developed a five-level safety culture maturity assessment framework. This study aims to investigate the conceptualization and foundation of developing safety culture maturity levels in the mining sector and provides an educational overview of the application of the developed model with five cultural maturity levels: basic, reactive, planned, proactive, and resilient. This research employs a systematic review methodology using the literature review method. Databases such as Google Scholar and Science Direct were utilized, focusing on specific keywords: "safety culture maturity level," "safety culture maturity level model," "safety maturity level," and "mining." Ten pertinent articles were examined as part of the review process. The methodology used in the development, evaluation, and implementation of safety culture maturity levels involved conducting interviews, utilizing matrices, Focus Group Discussions (FGDs), questionnaires, and literature reviews. The primary goal of the bulk of the publications included in the sample was to create a safety culture maturity level model suitable for application within the mining sector. The literature review revealed that the methodologies employed in these publications are aligned with the five levels of safety culture maturity as stated in Keputusan Dirjen Minerba Nomor 185 Tahun 2019. This comprehensive study discovered that the maturity assessment evaluation identified five identical safety culture maturity levels in each model advancement, consistent with Keputusan Dirjen Minerba Nomor 185 Tahun 2019 in the initial review part. The study provides clear and informative descriptions of the application of the five-level cultural maturity model in the mining sector.